Reframing the Responsiveness Challenge: A Framing-Anchored Explanatory Framework to Account for Irregularity in Novice Teachers' Attention and Responsiveness to Student Thinking. Issue 2 (2nd April 2020) - Richards, Jennifer; Elby, Andrew; Luna, Melissa J.; Robertson, Amy D.; Levin, Daniel M.; Nyeggen, Colleen G.
Abstract: Mathematics and science education researchers focused on teacher education emphasize attention and responsiveness to student thinking as central to effective classroom practice. Being responsive to student thinking involves attending to the substance of students' ideas—the meaning students are making—and pursuing that thinking, adjusting the flow of instruction as needed. Yet, attention and responsiveness to student thinking is irregular and generally rare among novice teachers. In this theoretical paper, we argue that the irregularity of attention and responsiveness to student thinking, including variability within individual teachers' practice, can be explained by a framework grounded in teachers' localized framings of their classroom activity—their sense of "what is it that's going on here." Using analyses of classroom episodes across contexts and timescales to illustrate our claims, we demonstrate how a framing-anchored framework can coordinate and improve upon three common explanations for the irregularity of novice teachers' attention and responsiveness to student thinking: underdeveloped skills and/or knowledge for attending and responding, "transmissionist" beliefs about learning, and institutional constraints (and teachers' perceptions thereof). Building on this argument, we suggest that teacher educators can work with novice teachers' framings of their classroom activities as a generative anchor for supporting attention and responsiveness to student thinking in classroom settings.